Deliberate Exercise of Pregnant Holstein Heifers Improves Milk Composition During Lactation - J. Johnson; P. Steichen; B. J. Bradford; A. E. Rhodes; T. G. Rozell (Kansas Agricultural Experiment Station Research Reports, 2019)
Exercise has substantial impacts on systemic physiology, but little research has been conducted to assess how it may influence dairy cattle in modern confined production systems. Dairy heifers were walked for up to 45 minutes, 4 days per week for 8 weeks during pregnancy to assess impacts on subsequent health and productivity. Heifers that were exercised had increased milk protein and solids-not-fat concentrations for up to 15 weeks into lactation, and increased milk fat and energy-corrected milk production at some time points during this period, as compared to sedentary contemporaries. No adverse or beneficial effects of exercise were found on locomotion, calving ease, date of parturition, or somatic cell scores. These findings point to potential impacts on lactation productivity following exercise in pregnant heifers.
Keywords: exercise; dairy heifers; milk; calving